1975
DOI: 10.3758/bf03209116
|View full text |Cite
|
Sign up to set email alerts
|

Approach tendency and threat display as related to social status of Siamese fighting fish,Betta splendens

Abstract: Forty-eight male Betta splendens were assigned to three groups of 16 (eight pairs) each. In two of the groups, pairs of fish were first allowed to fight until a dominance-subordinance relationship was established. Then each subject was tested on measures of time spent in approach and threat display toward either (1) its own pair member, with which it was experienced and familiar (Group EF), or toward (2) another combat-experienced fish, with which it was unfamiliar (Group EV). A third group of inexperienced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…Also, the current findings provide a plausible explanation for the result of Meliska et al (1975). Meliska et al (1975) arranged sue- cessive male-male pairings, with each of these encounters lasting 15 min. They appear to have found reliable individual differences in display, a finding supported by the current study.…”
Section: Resultsmentioning
confidence: 77%
“…Also, the current findings provide a plausible explanation for the result of Meliska et al (1975). Meliska et al (1975) arranged sue- cessive male-male pairings, with each of these encounters lasting 15 min. They appear to have found reliable individual differences in display, a finding supported by the current study.…”
Section: Resultsmentioning
confidence: 77%
“…I have presented evidence that, in at least some animal species, when this procedure is adopted, the measures of aggression and dominance status are not correlated. However, in two studies in which this protocol was used, aggression scores were found to predict dominance status (MELISKA et al 1975;EVANS 1985). In two other studies (BAENNINGER 1970;BARLOW et al 1986) aggressive behavior was found to predict dominance relationships under some conditions but not under others.…”
Section: Aggression's Limited Rolementioning
confidence: 99%
“…The finding, in Experiment 1, that subordinate fish are less inclined to view conspecifics than are more dominant fish, is consistent with the results of others. For example, when dominant and subordinate fish were permitted to view either familiar or unfamiliar opponents, Meliska et al (1975) reported that dominant fish spent more time approaching and displaying to their visual opponents than did subordinate fish. Also, Baenninger (1970) reported that dominant fish performed at a higher operant level than submissive fish when reinforcement was the opportunity to view a mirror.…”
Section: Discussionmentioning
confidence: 99%
“…Prior social experience has been operationally defined in a number of ways, including dominant and subordinate roles resulting from paired encounters (Baenninger, 1968(Baenninger, ,1970Lobb & McCain, 1976;Meliska, Meliska, Hoyenga, Hoyenga, & Ward, 1975), prior visual experience with a conspecific (Meliska & Meliska, 1976;Miley & Burack, 1977), and visual and combat experience with responsive or passive conspecifics and nonconspecifics (Johnson & Johnson, 1973).…”
mentioning
confidence: 99%